Dynamics in Classical Islamic Education: Between Nonformal Autonomy and Madrasah Hegemony (650–1250 CE) - Miftahur Rofi (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
Classical Islamic education played a central role in shaping the scientific architecture and social structure of Muslim societies from the 7th to the 13th century CE. Examining this period is essential for tracing the epistemological roots and institutional dynamics that continue to influence contemporary Islamic educational systems. This study employs a conceptual-analytical approach and a historical-critical method to investigate both formal institutions (madrasah) and informal ones (ḥalaqah, maktab, bookshops), including the characteristics of their curricula, modes of knowledge transmission, and the authority of teachers. The main findings reveal a dualism between the academic freedom of informal systems and the scholarly authoritarianism of standardized madrasah affiliated with state power. While informal education offered autonomy and flexibility in the pursuit of knowledge, both systems ultimately contributed to epistemological conservatism due to the dominance of textual authority and limited space for innovation. The implications suggest that the epistemic and political structures of classical Islamic education fostered a scholarly culture that was passive and resistant to interdisciplinarity. This study is limited in its geographical scope and does not fully address the dynamics of contemporary praxis. Therefore, a reconstruction of the Islamic educational system is needed—one that balances the authority of revelation and reason, and fosters a scientific ethos, intellectual freedom, and more transformative scholarly dialogue.